Institutionalization of Indonesia's Dark Social Movement in the Campaign Against the 2025 TNI Law: Dynamics and Strategies of Digital Resistance - Tsalitsa Haura Layyina; Nurain; Cindy; Aniqotul Ummah; Teddy Chrisprimanata Putra (ARRUS Journal of Social Sciences and Humanities, 2025)
This research presents analysis of the Indonesian Dark Social Movement which was institutionalized as a digital resistance to the 2025 TNI Bill considered to jeopardize civilian supremacy and democratic principles. Initially, the movement was formed by public dissatisfaction with the military's growing role in the civilian sector and the opaque legislative process, then it evolved into a digital movement with a common identity, communication strategies, and organized cross-platform coordination. Through qualitative approaches via documentation studies and content analysis of a variety of digital materials, the research draws a map of the dynamics of digital resource mobilization, narrative formation, and coordination that characterize the movement's institutionalization process. The results indicate that Indonesia Gelap was able to convert sporadic actions into a structured movement through symbolic consistency, internal division of roles, strategic use of digital platforms, and partnering with civil society networks. Nonetheless, this evolution faced difficulties in the form of government repression, misinformation, and inconsistencies in digital involvement. This research demonstrates that the digital environment is not only the outlet of people’s grievances but also the place where the adaptive and sustainable movement institutions are formed and this has consequences for social movements' overall strategies in the day of digital democracy.